Problematika Penerapan Kurikulum 2013 pada Lembaga Pendidikan Anak Usia Dini di Kecamatan Bululawang - Nurias Zetya Nawang Lupi (Universitas Trunojoyo Madura, 2017)
The Problem of Application of Curriculum 2013 At Early Childhood Education Institution In Bululawang Subdistrict. The curriculum is seen as the heart of an educational program. The curriculum can be viewed as a strategy and means designed to achieve nationally defined educational goals. All educators and managers of the early childhood should understand the framework and structure of curriculum 2013 Early Childhood Education for the implementation of early childhood programs in accordance with the goals set. But at this time there are still many early childhood education institutions that are still not able to apply the 2013 curriculum on learning activities. Seeing that, the researcher is interested to examine the problems of implementing the curriculum of early childhood institutions in kec. Bululawang Kab. Poor. This research uses qualitative research method, this research is conducted for 3 months, the problems are in the beginning starting from planning, implementation and evaluation of curriculum 2013 in PAUD institution. In the district of Bululawang Kab, Malang in the implementation of the lesson is still not much that apply the curriculum K13 due to lack of pemahan about curriculum 2013. In the implementation of the curriculum in 2013 the most important role is educators, the level of creativity of educators will affect the implementation of learning fun for children more creative teachers in conveying materials in the learning process, the easier the learner will receive the material delivered, that's where the success of the implementation of the 2013 curriculum in PAUD institutions.